The legacy of Franciscan observance convents in Portugal: Overview of their reuse towards sustainable development - Volzone, R.; Genin, S. (Regenerating cultural religious heritage: Intercultural dialogue on places of religion and rituals, 2022)
he legacy of St. Francis of Assisi (1181/82–1226) still survives through his rules and spiritual texts, as well as in the architectural structures built by the Fran-ciscan order, with their surrounding landscape and territory. The gradual abandon-ment of religious houses, culminating with the definitive dissolution of the Portuguese religious orders in 1834, led to the loss of their original function and values. Most of the over 400 Franciscan complexes identified through previous research have been altered or abandoned, are in a ruinous state, or have disappeared. Sometimes they are unknown, even to the local inhabitants. This study presents an overview of the 33 scattered Franciscan Observance conventual cultural heritage sites. Upon identi-fying the settlements, we undertook a census of the existing physical structures, with analysis of their owners, conservation state, and reuse. Generally, no adequate anal-ysis had been carried out before proceeding with works that profoundly transformed the ancient conventual structures. More thoughtful reuse of these structures would respect their integrity and authenticity, benefitting local communities in a sustainable way, promoting inclusive economic growth by reducing inequalities.